2009
DOI: 10.1097/tp.0b013e3181aa6c9b
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Early Loss of Transplanted Islets in the Liver of Mice by Adenosine

Abstract: Adenosine suppresses the NKT cell-mediated IFN-gamma production of neutrophils in the liver of mice receiving islets, thus leading to prevention of early loss of transplanted syngenic and allogenic islets. The findings indicate that adenosine may improve efficiency of clinical islet transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Intraperitoneal glucose tolerance test was performed as described (28). Briefly, mice fasted for 12 h, during which baseline blood glucose levels measured, they were injected intraperitoneally with 10% glucose in PBS (3 g/kg body weight), and blood glucose was determined.…”
Section: Methodsmentioning
confidence: 99%
“…Intraperitoneal glucose tolerance test was performed as described (28). Briefly, mice fasted for 12 h, during which baseline blood glucose levels measured, they were injected intraperitoneally with 10% glucose in PBS (3 g/kg body weight), and blood glucose was determined.…”
Section: Methodsmentioning
confidence: 99%
“…In their investigation of the effect of adenosine therapy in islet transplantation, Nitta et al . demonstrated that a single dose of adenosine delivered at the time of islet transplantation suppressed NKT cell-mediated IFN-g production by Gr-1 + CD11b + cells (neutrophils) in the liver of streptozotocin-induced diabetic recipient mice, thus preventing early loss of transplanted syngeneic and allogeneic islets and enabling transplantation using a single donor [141]. This observation combined with the observation of Lappas et al .…”
Section: Strategies To Reverse/prevent Type 1 Diabetes Mellitusmentioning
confidence: 98%
“…However, in contrast, studies by Nitta et al . indicate the involvement of NKT cells in both syngeneic and allogeneic immune rejection of islet allografts in the liver of mice and demonstrate the immunosuppressive role of adenosine in preventing NKT cell-mediated destruction of islet grafts [141]. Recently, a new subset, iNKT17 cells, that produce high levels of the pro-inflammatory cytokine IL-17 implicated in several autoimmune diseases, has been identified [142].…”
Section: Pathogenesis Of Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…Several studies indicate that inhibition of non specific inflammation improves the function and survival of islet grafts. For instance, Yasunami's group demonstrated that V-alpha14 NKT cell-triggered IFN- γ production by Gr-1+CD11b+ cells mediated early graft loss of syngeneic transplanted islets [94]. Adenosine administration suppressed NKT cell-mediated IFN- γ production of neutrophils in the livers of graft-recipient mice, leading to prevention of early loss of transplanted syngeneic and allogeneic islets.…”
Section: Islet Transplantationmentioning
confidence: 99%